TECHNICAL FEASIBILITY AND ECONOMICS OF DIRECT APPLICATION OF THE NIGERIAN TAR SAND DEPOSITS AS ROAD ASPHALT - Akinmosin, A.; Olufowobi, S. O. (UNILAG Journal of Medicine, Science and Technology, 2019)
This study present, the technical feasibility and the Economics of the direct application of Nigerian Tar sand deposits as road asphalt. Twenty Tar sand samples were selected from nine locations in parts of Southwestern Nigeria and several engineering tests were conducted on twenty samples. The tests involved Bitumen extraction to determine the percentage of bitumen content, Sieve analysis, Specific gravity and Marshall tests which include the Stability, Flow, Density and Void determination. The percentage of bitumen saturation ranges from 5.6 to 28.6%, the stability values ranges from 2.1 to 6.3KN, the flow values ranges from 27.8 to 63.1mm10, specific gravity values ranges from 1.79 to 2.35g/ml and density values ranges from 1.75 to 2.01g/ml. The sieve analysis results indicate that none of the samples could be applied directly in road construction, though some of them possess stability and flow values that meet the standard specification for wearing course of asphalt. Design mix analysis which involves modification of mineral aggregates was carried out on ten out of the twenty samples to improve their gradation. From economic point of view, using the modified aggregates of tar sand (@?7,000-9,500 per ton) as against current asphalt concrete (?20,000 per ton) would have potentially large cost saving in Nigeria.